2018
DOI: 10.15694/mep.2018.0000041.1
|View full text |Cite
|
Sign up to set email alerts
|

Professional Identity Formation in medical school: One measure reflects changes during pre-clerkship training

Abstract: Professional Identity Formation (PIF), the process of internalizing a profession's core values and beliefs, is an explicit goal of medical education. The Professional Identity Essay (PIE), a developmental measure of the extent to which individuals have a complex and self-defined understanding of their professional role, is a tool to both study and scaffold PIF. PIE staging has internal reliability and response process validity and correlates with a validated measure of moral reasoning. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 30 publications
(61 reference statements)
1
42
0
4
Order By: Relevance
“…De‐identified essays were scored by an adult developmental educational psychologist based on the Kegan's Subject‐Object Interview platform for assessing the adults' identity development (Kegan, ). This study found that 46% of students in this medical class remained at the same stage in their professional development and 15% of students scored lower than at the time of matriculation to medical school (Kalet et al, ). While we can all hope that these results are not the norm, the prospect that half of our trainees might remain stagnant in their PIF through their first two years of training poses a distinct challenge to medical educators.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…De‐identified essays were scored by an adult developmental educational psychologist based on the Kegan's Subject‐Object Interview platform for assessing the adults' identity development (Kegan, ). This study found that 46% of students in this medical class remained at the same stage in their professional development and 15% of students scored lower than at the time of matriculation to medical school (Kalet et al, ). While we can all hope that these results are not the norm, the prospect that half of our trainees might remain stagnant in their PIF through their first two years of training poses a distinct challenge to medical educators.…”
mentioning
confidence: 86%
“…Cruess et al () espouse the development of professional identity as a new principal goal for medical education. Now several reflective tools designed to measure the PIF have been developed (Bebeau and Monson, ; Kalet et al, , ). Nonetheless, much work apparently needs to be done.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For quantitative analysis, the PIF levels for norms and values of professionalism were measured using PIE, an essay-based measurement tool with 9 question items. Referring to Dr. Kalet and colleagues' rubric [28] based on Kegan's identity stage [28,29], assessors chose learners' professional identity levels from Stage II to II/III, III, III/IV, IV, IV/V, and V. The PIF measurement by PIE has been validated in undergraduate settings [28,31]. In this study, we used a Japanese version of the PIE form and rubric (PIE-J) originally in English.…”
Section: Instruments 1) Pif Data Collectionmentioning
confidence: 99%
“…Notably, research has considered how professional identities may influence a wide range of attitudes on issues pertaining to ethical standards, new technology adoption in the clinical context (Mishra et al 2012;Keller et al 2016) and professional commitment (Molleman and Rink 2015;van Os 2015). In terms of developmental issues, professional identities formation research explores how medical students and junior doctors' professional identities are impacted by early formative experiences and can be developed through educational initiatives aimed at fostering professional identities (de Lasson et al 2016;Monrouxe 2016;Monrouxe et al 2017;Kalet et al 2018). While the contributions of this body of work should not be overlooked, understanding the core question of what encompasses physicians' professional identities is relatively under investigated.…”
Section: Introductionmentioning
confidence: 99%